Penerapan Model Learning Cycle Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA Kelas V SD Negeri 227 Bera Kabupaten Soppeng - Rasmi Djabba; Nur Ilmi (Universtas Negeri Makassar, 2022)
This study examines the application of the Learning Cycle Model to improving student learning outcomes in science subjects for class V SD Negeri 227 Bera. The main problems studied are how the process of implementing the Learning Cycle in increasing student learning activities in science subjects about the properties of light in class V and whether the application of the learning cycle can improve student learning outcomes in science subjects about the properties of light in class V. The approach used is a qualitative approach and the type of research used is Classroom Action Research (CAR). The focus of the research is the activities of teachers and students by applying the Learning Cycle to science subjects and science learning outcomes. The subjects of this study were teachers and students of class V. There were 15 students consisting of 10 boys and 5 girls. Data collection techniques used are observation, tests, and documentation. Based on the type of research used, namely classroom action research which consists of planning, implementation, observation and reflection. The research data obtained in the first cycle are only less qualified (C), then an increase in the second cycle becomes good qualification (B) The conclusion from the results of this study is that applying the Learning Cycle can improve student learning outcomes in science subjects in class V .